Leading boarding school quality management (Multisite study of man Insan Cendekia Serpong and Smanu Mh Thamrin Jakarta) - Kharismawaty, Kartika; Fuad, Nurhattati; Ahmad, Masduki (Edelweiss Applied Science and Technology, 2024)
The research objectives are 1). Analyzing the planning of the learning process in improving the quality of boarding school education. 2). Analyzing the implementation of the learning process in improving the quality of boarding school education. 3). Analyzing authentic supervision and assessment (authentic supervision and assessment) of the learning process in improving the quality of boarding school education. 4). Analyzing improvements in the quality of the learning process in improving the quality of boarding school education in improving the quality of education owned by MAN Insan Cendekia Serpong and SMANU MH Thamrin Jakarta. The research method uses a qualitative approach by collecting data through observation, interviews and documentation to obtain accurate data. This research was conducted at MAN Insan Cendekia Serpong and SMANU MH. Thamrin Jakarta. Results of research on the quality management of leading boarding schools, a multisite study by MAN Insan Cendekia Serpong and SMANU MH. Thamrin Jakarta. The research results show that the quality of education services in schools is in accordance with national education standards. The relationship between quality and service is closely related to accreditation, curriculum and strategic plans.